Can contract farming in organic basmati rice be a boon to smallholders? Evidence from India - Mishra, Ashok K.; Kumar, Anjani; Joshi, Pramod Kumar; D'Souza, Alwin; Tripathi, Gaurav (International Food Policy Research Institute, 2018)
Demand for organic basmati rice (OBR), both at home and abroad, coupled with policy reforms in India have given rise to contract farming (CF) production in that nation. OBR production, however, is highly susceptible to weather and pest risks. This study investigates the impact of smallholders’ perceived production risks on their adoption of CF in OBR farming. We also assess the impact of CF in OBR production on yields, prices received, and the livelihood of OBR producers. We use farm-level data from smallholder basmati rice farms in India and the endogenous switching regression method to account for heterogeneity.